2008
DOI: 10.1099/ijs.0.65645-0
|View full text |Cite
|
Sign up to set email alerts
|

Cloacibacillus evryensis gen. nov., sp. nov., a novel asaccharolytic, mesophilic, amino-acid-degrading bacterium within the phylum 'Synergistetes', isolated from an anaerobic sludge digester

Abstract: Cloacibacillus evryensis gen. nov., sp. nov., a novel asaccharolytic, mesophilic, amino-acid-degrading bacterium within the phylum 'Synergistetes', isolated from an anaerobic sludge digester T were non-motile, rodshaped (2.0-3.0 ¾ 0.8-1.0 mm) and stained Gram-negative. Optimal growth occurred at 37 6C and pH 7.0 in an anaerobic basal medium containing 1 % Casamino acids. Strain 158 T fermented arginine, histidine, lysine and serine and showed growth on yeast extract, brain-heart infusion (BHI) medium and trypt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
51
0
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(57 citation statements)
references
References 31 publications
(39 reference statements)
4
51
0
2
Order By: Relevance
“…They are able to ferment proteins or amino acids to produce VFAs, H 2 , and CO 2 (Ganesan et al 2008;Looft et al 2013). It was found that Aminobacterium played a dominant role in a methanogenic digester containing bovine serum albumin as a sole carbon source (Tang et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…They are able to ferment proteins or amino acids to produce VFAs, H 2 , and CO 2 (Ganesan et al 2008;Looft et al 2013). It was found that Aminobacterium played a dominant role in a methanogenic digester containing bovine serum albumin as a sole carbon source (Tang et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…EF559200), from a T and related genera of the phylum Synergistetes Taxa: 1, strain 4F6E T (data from this study); 2, Aminiphilus (Díaz et al, 2007); 3, Aminobacterium (unless indicated, data from Baena et al, 1998Baena et al, , 2000; 4, Aminomonas (Baena et al, 1999b); 5, Anaerobaculum (Rees et al, 1997;Menes & Muxí, 2002;Maune & Tanner, 2012); 6, Cloacibacillus (Ganesan et al, 2008); 7, Dethiosulfovibrio (unless indicated, data from Magot et al, 1997;Surkov et al, 2001;Díaz-Cárdenas et al, 2010);8, Fretibacterium (Vartoukian et al, 2013);9, Jonquetella (Jumas-Bilak et al, 2007); 10, Pyramidobacter (Downes et al, 2009);11, Synergistes (Allison et al, 1992); 12, Thermanaerovibrio (Guangsheng et al, 1992;Baena et al, 1999a;Zavarzina et al, 2000); 13, Thermovirga (Dahle & Birkeland, 2006). +, Positive; 2, negative; ND, no data available.…”
Section: Strain 4f6ementioning
confidence: 99%
“…When grown on serine or pyruvate, Aminobacterium mobile produces alanine in addition to acetate (Ganesan et al, 2008). Cloacibacillus evryensis produces acetate, butyrate and small amounts of propionate and valerate by fermenting serine and histidine (Ganesan et al, 2008). Strain 4F6E…”
Section: Strain 4f6ementioning
confidence: 99%
See 1 more Smart Citation
“…C. evryensis was isolated from an anaerobic digester of a wastewater treatment plant (1); C. porcorum was isolated from the mucosal lining of a pig cecum (2). Members of this genus can be identified by 16S rRNA gene sequencing, cellular fatty acid profiles, DNA GϩC content, and metabolic end product analysis (1). The genus Cloacibacillus is a member of the family Synergistaceae in the phylum Synergistetes, which was described in 2009 (3).…”
mentioning
confidence: 99%